Primary Motor Cortex Excitability in Karate Athletes: A Transcranial Magnetic Stimulation Study - Monda, Vincenzo; Valenzano, Anna; Moscatelli, Fiorenzo; Salerno, Monica; Sessa, Francesco; Triggiani, Antonio I.; Viggiano, Andrea; Capranica, Laura; Marsala, Gabriella; De Luca, Vincenzo; Cipolloni, Luigi; Ruberto, Maria; et al. (Frontiers in Physiology, 2017)
Purpose. Transcranial magnetic stimulation (TMS) has been largely used to investigate adaptive changes in human motor cortex, and to understand how networks in the brain build and optimize motor programs responsible for coordination of muscle activity involved in complex motor learning. Karate represents a valuable model to investigate the effects of training on the corticospinal system excitability, because it requires a high level of coordination. The aim of this study was to examine possible changes in the resting motor threshold (rMT) and in the corticospinal response in karate athletes, and if athletes are characterized by a specific value of rMT. Methods. Twenty-fiveright-handed male karate athletes (24.9±4.9 years) and twenty-five matched non-athletes (26.2±4.5 years) were recruited. TMS was delivered over the metacarpal area of the left primary motor cortex, corresponding to the first dorsal interosseous muscle. Motor evoked potential (MEP) latencies and amplitudes at rMT, 110%, and 120% of rMT were considered. Results. Compared to non-athletes, athletes showed a lower resting motor threshold (p<0.01), shorter MEP latency (p<0.01) and higher MEP amplitude (p<0.01). Moreover, the roc curve was significant (p<0.001; sensitivity 84%, specificity 76%). Conclusions. The main finding of the present study was that there are significant differences in cortical excitability between athletes and non-athletes. Athletes’ changes in rMT and MEP values might be the result of plasticity of the motor cortex, due to sport practice which improves cortical excitability. These finding support the hypothesis that training determines specific brain organizations to meet specific sport challenges.